1995
DOI: 10.1149/1.2050055
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Both Carbon Supports and Heat‐Treatment of Supported Catalyst on Electrochemical Oxidation of Methanol

Abstract: The effects of carbon supports for platinum-ruthenium (Pt-Ru) catalysts on anode performance of direct methanol fuel cells (DMFC) were investigated. Good polarization characteristics of the methanol electrode were obtained for a Pt-Ru catalyst supported on an acetylene black with high specific surface area and a pore size distribution in the range of 3 to 8 nm. The performance of the methanol electrode increased with the increase in pore volume for the pore size distribution of 3 to 8 nm. Analyses of various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(64 citation statements)
references
References 0 publications
1
60
0
3
Order By: Relevance
“…The most often utilised catalyst support materials for PEMFC are carbon blacks, whose properties and suitability for PEMFCs were examined in a number of publications ( [1] and references therein, [4,5]). In search of better catalyst supports, various novel carbon materials, such as carbon nanotubes and nanofibers [6], ordered mesoporous carbons [7,8] and disordered mesoporous carbons, such as Sibunit [9,10], were recently evaluated in the fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…The most often utilised catalyst support materials for PEMFC are carbon blacks, whose properties and suitability for PEMFCs were examined in a number of publications ( [1] and references therein, [4,5]). In search of better catalyst supports, various novel carbon materials, such as carbon nanotubes and nanofibers [6], ordered mesoporous carbons [7,8] and disordered mesoporous carbons, such as Sibunit [9,10], were recently evaluated in the fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, an important role is played by the carbon support. In fact, the carbon support should have a high percentage of mesopores in the 20-40 nm region to provide a high accessible surface area to catalyst and to the monomeric units of the Nafion ionomer to boost the diffusion of chemical species [33][34][35]. The influence of both porosity and texture of the carbon support have influence on mass transport losses.…”
Section: Influence Of the Carbon Support On The Catalytic Activity Ofmentioning
confidence: 99%
“…It has been observed for Pt/C catalysts, synthesized using the sulphite-metal complex method, that platinum particles size decreased with increasing the specific surface area of the carbon black [34]. Instead, when the metal deposition on the carbon support is performed by impregnation methods, the specific surface area of the carbon support seems to have only a little effect on Pt dispersion [53].…”
Section: Carbon Blacksmentioning
confidence: 99%
“…Wu et al [21] reported that electrocatalytic efficiency of Pt nano particles also depends on the supporting matrix. Generally carbon and carbon-based materials are used for supporting catalyst particles [22][23][24][25][26][27][28][29][30]. A thin film of electronically conducting polymer (CP) acts as a good dispersing material for Pt nanoparticles [31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%